Red blood cell alloantibodies detection in malay pregnant women and haemolytic disease of fetus and newborn - Hassan, Mohd Nazri (2011)
Pregnancy is known to cause red blood cell (RBC) alloimmunisation which may lead to the production of harmful alloantibodies and a subsequent potential for causing haemolytic disease of fetus and newborn (HDFN). However, RBC alloantibodies are significantly different between different populations and ethnic groups. The aim of this study is to determine the prevalence of RBC alloantibodies among Malay pregnant women and their association with HDFN. Clinical and serological data of 5163 Malay pregnant women who attended labour room, Hospital Universiti Sains Malaysia from January to December 2009 were collected and analyzed prospectively. The blood samples were subjected to the standard immunohaematological procedure for red cell antibody screening and identification. The newborns of women with positive antibody screening were monitored for the evidence of HDFN. Fifty one (0.99%) pregnant women were found to have irregular RBC alloantibodies andwhen the specificities were further characterized, 30 (0.58%) women were found to possess clinically significant alloantibodies. Most of the clinically significant alloantibodies belonged to Rhesus (Rh) system (55.8%) where anti-E (33.3%) was the most common antibody identified, followed by anti-D (10.0%). There was significant association between RBC alloimmunisation in Malay pregnant women and RhD blood group, history of abortion, preterm labour, APH, IUD and history of blood transfusion. Fourteen (0.27%) neonates were clinically diagnosed as HDFN. Anti-D, anti-c and anti-K were identified to cause moderate to severe HDFN. In conclusion, prevalence of RBC alloantibody in Malay pregnant women is low (<1%), which is similar to other published studies. There were differences in the distribution of alloantibody specificity, however the antibodies toward Rh antigen are still the commonest clinically significant alloantibody identified. Considering the low prevalence of clinically significant alloantibodies and HDFN, the value of current routine antenatal RBC antibody screening practice in most Western countries becomes questionable and may not be directly applicable to Malaysian community without some modification. It is recommended that the antibody screening test should be restricted to women who are RhD negative, or with past history of HDFN especially due to anti-c and anti-K.